Unraveling short-lived rejuvenated volcanism and a rapid transition from shield stage at O'Higgins Guyot, Juan Fernández Ridge, Pacific SE. (November 2018) - Lara, Luis E.; Díaz-Naveas, Juan; Reyes, Javier; Jicha, Brian; Orozco, Gabriel; Tassara, Andrés; Kay, Suzanne
Abstract: Rejuvenated volcanism is a common and usually low volume stage in the archetypical evolution of oceanic islands. Magmas related to this transient stage are mostly alkaline with a more depleted source than the mantle plume that fed the shield stage. Being ubiquitous in oceanic islands, only a few rock samples with geochemical features of post-erosional volcanism have been recovered from seamounts worldwide, although usually with a great uncertainty about the eruptive age and the stratigraphic framework. Here we report on the finding of a young, subaqueous lava flow with a fresh morphology as shown in high-resolution bathymetry, just on top of the O'Higgins Guyot, Juan Fernández Ridge in the SE Pacific. Basanite rocks recovered are quite similar to other post-erosional lavas recognized along the Juan Fernández Ridge, and were dated at ca . 8.2 Ma, only slightly younger than the youngest, shield stage section of the 8.5–9.3 Ma guyot. Such a rapid transition calls for a process explaining both the summit erosion of the shield volcano and the subsequent volcanism with a different magma source and/or melting process in a narrow time window. Isostatic rebound and subsequent flexural deformation may have triggered partial melting of the mantle source just below the seamount, with rapid ascent assisted by the same structural conditions but precluded shortly after. Highlights: Lavas with signature of rejuvenated volcanism were sampled on top of the O'Higgins guyot. A rapid transition from shield to rejuvenated stage was found with 40 Ar/ 39 Ar dating rejuvenated. Rapid is interpreted as a result of sector-collapse and isostatic rebound deformation.